Rethinking the relationship between housing prices and inflation: new evidence from 29 large cities in China - Tang, Jianli; Ye, Kunhui; Qian, Yan (International Journal of Strategic Property Management, 2019)
This paper presents a longitudinal analysis of the relationship between housing prices and inflation by employing new housing price indices from 29 large Chinese cities over the 2003–2013 period. Based on the Autoregressive Distributive Lag (ARDL) model and bounds test, we find no long-run co-integration relationship between housing prices and inflation. This result is robust for different types of inflation (actual, expected, unexpected inflation). Furthermore, it is found that the housing prices in China grow spectacularly in the sample period owing to the dramatic development of the Chinese economy, while inflation grows in a more modest way. Although the study is conducted in the context of China, the results can provide useful evidence to the debate on the relationship between housing prices and inflation.